INFLUENCE OF FAMILY DYNAMICS ON METHAMPHETAMINE USAGE AND MENTAL HEALTH - Tongawaji, ThankGod Josiah; Chinawa, Francis Chukwuemeka (Academic Journal of Psychology and Education (AJPE), 2025)
Methamphetamine use is a growing public health concern associated with severe mental health challenges such as anxiety, depression, and psychosis. This study examined the influence of family dynamics on methamphetamine usage and mental health among in-patients and out-patients in mental health facilities in Port Harcourt, Nigeria. A cross-sectional survey design was employed, and data were collected from 83 respondents using structured questionnaires, including the Drug Abuse Screening Test (DAST-10), Index of Family Relations (IFR) Scale, and Self-Reporting Questionnaire (SRQ-20). Findings revealed that 79.5% of the respondents were male, and 78.3% came from polygamous family backgrounds. A significant proportion (90.4%) exhibited high or severe methamphetamine use, while 88.0% displayed symptoms of mental health distress. Pearson correlation analysis showed a statistically significant relationship between family dynamics and methamphetamine use (r = 0.512, p < 0.01) as well as between family dynamics and mental health distress (r = 0.530, p < 0.01). The study highlights that dysfunctional family structures, poor parental supervision, and adverse childhood experiences contribute to increased substance abuse and mental health challenges. Based on these findings, the study recommends family-centered interventions, including improved communication, conflict resolution, and emotional support programs. Healthcare providers should integrate family assessments into substance abuse and mental health treatment plans. Additionally, policymakers should allocate resources for family therapy and substance abuse prevention programs. Further research is required to explore causal relationships, cultural differences, and the effectiveness of family-based interventions in mitigating substance abuse and improving mental health outcomes